Development of Interactive Multimedia on Science Learning Based Adobe Flash CS6 - Sukariasih, Luh; Erniwati, Erniwati; Salim, Agus (Universitas Malikussaleh, 2019)
The purpose of this study to to produce multimedia of science learning in the topic of pressure the circulatory system and respiratory system in humans for students of junior high school class of VIII. In this study uses a Research and Development model that refers to the model of Analysis, Design, Development, Implementation, and Evaluation (ADDIE). In the phase of analysis; a needs analysis, material analysis, and analysis of the level of ability and characteristics of the aim users carried out. Design Phase: create flowcharts and storyboards. At the stage of development, multimedia made. The phase of Implementation, multimedia that has been made validated by experts and limited trials. In the phase of evaluation; at this stage, the multimedia that has been implemented thoroughly evaluated. The evaluation results used to see the level of achievement linked the objectives set at the beginning of the program — data collection techniques used in the form of questionnaires. The data sources in this study consisted of 2 material experts, four media experts, two learning experts, and tested limited to 2 teachers and 18 students from junior high school 8 Kendari. The expert trial results stated that Adobe Flash CS6-based the multimedia of Science learning on pressure material in the circulatory and respiratory systems in humans for students of Class VIII junior high school was under the design, and the material included inappropriate used as science learning multimedia. The results of a limited trial show that the multimedia of science learning in the material of pressure in the circulatory system and the respiratory system in humans is worthy used as a multimedia learning science